2016
DOI: 10.1126/science.aaf4822
|View full text |Cite
|
Sign up to set email alerts
|

IgA production requires B cell interaction with subepithelial dendritic cells in Peyer’s patches

Abstract: Immunoglobulin A (IgA) induction primarily occurs in intestinal Peyer’s patches (PPs). However, the cellular interactions necessary for IgA class switching are poorly defined. Here we show that in mice, activated B cells use the chemokine receptor CCR6 to access the sup-epithelial dome (SED) of PPs. There, B cells undergo prolonged interactions with SED dendritic cells (DCs). PP IgA class switching requires innate lymphoid cells, which promote lymphotoxin-β receptor (LTβR)-dependent maintenance of DCs. PP DCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
270
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(301 citation statements)
references
References 48 publications
15
270
2
Order By: Relevance
“…IgA production was augmented by the interaction between B-cells and DCs in Peyer's patches through integrin avb8-activated TGF-b [48]. This was confirmed by the finding that IgA class-switch by B-cells in Peyer's patches was impaired in CD11c-Cre Itgb8 fl/fl mice and by treatment with an avb8-blocking antibody [48].…”
Section: Tgf-b In B-cells Mediates Iga Class-switch and Promotessupporting
confidence: 70%
“…IgA production was augmented by the interaction between B-cells and DCs in Peyer's patches through integrin avb8-activated TGF-b [48]. This was confirmed by the finding that IgA class-switch by B-cells in Peyer's patches was impaired in CD11c-Cre Itgb8 fl/fl mice and by treatment with an avb8-blocking antibody [48].…”
Section: Tgf-b In B-cells Mediates Iga Class-switch and Promotessupporting
confidence: 70%
“…Whether in vivo B cell-derived TGF-b1 is the exclusive source of TGF-b1 for IgA switching cannot be inferred from our experiments. Of note, it was recently reported that IgA production in murine Peyer's patches requires interaction of B cells with subepithelial dendritic cells expressing integrin aVb8, which activates latent TGF-b produced by an undefined cellular source (29). Garp/latent TGF-b1 complexes on the surface of murine B cells themselves could represent a source of latent TGF-b1, available for activation in trans by integrin aVb8 on the surface of dendritic cells.…”
Section: Resultsmentioning
confidence: 99%
“…ILC3 resident in Peyer's patches and intestinal lymphoid structures play key roles in the regulation of IgA production in the intestinal tract, via lymphotoxin‐dependent mechanisms 41, 105, 106, 107. LTi‐like ILC3 express both membrane‐bound lymphotoxin heterotrimers (LT α 1 β 2 ) as well as soluble lymphotoxin α homotrimers (LT α 3 ), which control T‐independent and T‐dependent IgA responses, respectively 105, 106. Human and mouse splenic ILC3 also stimulate innate‐like B‐cell IgG production through CD40 interactions, production of BAFF/APRIL and via the Notch ligand Delta‐like 1 108, 109.…”
Section: Ilc3 Interactions With Adaptive Immunitymentioning
confidence: 99%